Analisis Proses Pemecahan Masalah Geometri Berdasarkan Teori Van Hiele di Sekolah Menengah Atas - Indah, M.E.B (Jurnal Noken: Ilmu-Ilmu Sosial, 2016)
This study aims to explore and describe the process of problem solving geometry reach the level of visualization, analysis and informal deduction based on the Van Hiele theory. This type of research is descriptive explorative and qualitative approach. Subject of the study was obtained from the high school students who were tested on the level of Van Hiele geometry. Each level of visualization, analysis and informal deduction taken two learners who can communicate well. The results of this study indicate that solving problems in geometry learners who attained think visualization is to identify problems and set goals using the language question. Troubleshooting on the geometry of learners who attained think the analysis is through fifth troubleshooting step IDEAL using their own language, but less systematic. Troubleshooting on the geometry of students who reach a level of thinking is through the informal deduction fifth troubleshooting step IDEAL by systematically using their own language.